MENINGKATKAN KETRAMPILAN MENULIS NARASI DENGAN MENGGUNAKAN MEDIA FILM ANIMASI PENDEK (Penelitian Tindakan Kelas pada Mahasiswa Semester II Kelas 02 Prodi Pendidikan Bahasa Inggris FKIP UNISRI Tahun ajaran 2012/2013) - Istianasari, Ayu (UNIVERSITAS SLAMET RIYADI, 2014)
This research is written 1) to know whether or not short animation film improve the students' writing skill on narrative text and 2) to describe the class situation when short animation film is implemented in the writing class at the second semester students of English Department in the academic year of 2012/2013. The method used in this research was classroom action research. The research was conducted in two cycles. Every cycle consisted of four steps; planning, implementing, evaluation, and reflection. In collecting the qualitative data, the researcher used observation, questionnaires, interviews, and field notes. In collecting the quantitative data, the researcher used tests (pre-test and post-test). The qualitative data consists of five steps: assembling the data, coding, comparing, building interpretations, and finally reporting the outcomes. Meanwhile, the quantitative data were analyzed using a descriptive statistic technique. The research findings prove that animation movies could improve the students' writing skill of narrative text and the class situation. 1) The improvement of the students' writing skill included: Â (a) The students got easy in exploring ideas in their writing, (b) They could produce the sentences with the better construction and minimize their mistake in English grammar, (c) They were able to use the appropriate word order and used the various words to express their ideas well, (d) They could state the ideas more clearly, organized the ideas better than previous result, used logical sequencing and produced text well in good cohesion and coherence, (e) They were able to demonstrate the convention and minimize the errors and mistakes of spelling, punctuation, and capitalization. 2) The improvement of class situation included: (a) The students focused seriously on their tasks, (b) They involved and participated actively during the lesson, (c) They became more confident in doing the activities during lesson, (d) They were more enthusiastic and were motivated in joining the writing class, (e) They were not getting bored or made noise but they looked happy in the writing class. The mean score had the advancement from the pre-test to the post-test 2. Â In the pre-test the students got 65, while in the post test 1 they got 72 and in the post-test 2 they got 80.